Severe Mental Disorders from a Cognitive-Behavioural Perspective: A Comprehensive Review from Conceptualization to Intervention - Tavares, Sofia (Current Psychiatry Reviews, 2017)
Research has shown that hallucinations and delusions (characteristic of severe mental disorders) are relatively common. Many people in the general population will experience mild instances of such events at some point in their lives. However, for others, these are very disturbing events. Cognitive-behavioural models argue that these differences result from the interpretation of those same experiences. Therefore, cognitive behavioural therapy seeks to know the factors that contribute to the development (e.g. early traumatic experiences) and maintenance (e.g. selective attention, safety behaviours, disruptive control strategies) of psychotic processes, from the deep and isolated understanding of each patient's experience of specific symptoms (e.g. paranoid delusions) rather than their syndromal diagnosis (e.g. schizophrenia). The case formulation for each complex psychotic symptom results from the initial intake assessment at the start of a prospective intervention. This article reviews the cognitive behavioural conceptualization of psychotic symptoms (i.e. auditory hallucinations, delusions and negative symptoms), as well as the key areas of assessment and therapeutic interventions proposed by these models.
Keywords: Cognitive-behavioural therapy